Response of supplemental cassava root sievate - cassava leaf meal based diets on carcass and cost benefits of kano brown goats Capra aegagrus - Ahaotu E. Obioha; Okorie Kennedy; Akinfemi Abayomi; Emeribe E. Okechukwu (Aceh Journal of Animal Science, 2018)
The experiment was conducted to determine the organ weight characteristics, carcass yield and cost benefits of Kano Brown goats fed cassava root sievate and cassava leaf meal (CRSCLM) based diets as supplement to (Pennisetum  purpureum) using 36 Kano Brown goats of 8 to 10 months of age.Four diets T1, T2, T3,and T4, were formulated at the levels of 0%, 20%, 40% and 60% CRSCLM respectivelyin a completely randomized design. Each animal received a designated treatment diet in the morning for 97 days. Feed offered was based on 3.5% body weight per day; the animals in addition were fed a kg wilted chopped P. purpureum later in the day as basal diet to enhance rumination and fine chewing. Results on  carcass indices showed significant (p0.05) response on live weight at slaughter, empty carcass weight, warm carcass weight, dressing percentage, shoulder, leg, loin, end and shank with T4having relatively best results. The dressing percentage was numerically (49.59%) best at T4. On the offal weights, head and full guts were significantly (p0.05) improved for T4and T1goats. The organ characteristic proved the safety of using CRSCLM through the significantly (p0.05) lower organ weights at T4goats. Cost per kg feed, feed cost/weight gainand cost/benefit ratio were positively influenced (p0.05) at T4with expected income of 4.79 / 1 invested. It could therefore be concluded that Kano Brown goats fed 60% CRSCLM had the best carcass and organ yields at a reduced feed cost. Keywords: Pennisetum purpureum, Kano brown goats, Cassava leaf meal, Cassava root sievate,